(untitled) (KULT_online, 2022)
With their book Memes – Formen und Folgen eines Internetphänomens, Joanna Nowotny and Julian Reidy offer an insightful contribution to the still relatively little researched field of memes in cultural studies. Their study illustrates how diverse and socially relevant the subject area is. The authors extensively analyze a variety of examples, thereby demonstrating that memes are much more than funny images with text.